Attracting Chinese FDI in Africa: The role of natural resources, market size and institutional quality. Issue 2 (26th January 2018) - Shan, Shan; Lin, Zhibin; Li, Yulei; Zeng, Yan
Abstract : Purpose: The purpose of this paper is to examine the effect of natural resources, market size and five major institutional factors (voice and accountability; political stability and absence of violence; regulatory quality; rule of law and control of corruption) on Chinese foreign direct investment (FDI) in Africa. Design/methodology/approach: This study uses regression analysis on panel data across 22 countries for the period 2008-2014. Findings: Natural resources did not play a significant role in attracting Chinese investments, but market size did. Among the institutional factors, only voice and accountability had a significant and positive effect on attracting Chinese FDI; the effects of rule of law and control of corruption were not significant and political stability and regulatory quality had a significant and negative effect. Research limitations/implications: Chinese investment in Africa is only a recent phenomenon, and is growing rapidly; further studies should examine factors that are unique to the context such as bilateral political link. Practical implications: African countries that are struggling with improving their poor institutional quality in the short term could effectively attract Chinese investment by reducing investor psychic distance, e.g. establishing a closer political link with China. Nevertheless, in the long term, measures of improving institutional quality are important. Originality/value: This study reveals for the first time that what attracts Chinese investment is market size rather than natural resources, and different institutional factors of an African country show varying effects on attracting Chinese FDI.